Offshore Technology Conference 2005
DOI: 10.4043/17670-ms
|View full text |Cite
|
Sign up to set email alerts
|

Steel Catenary Riser Design and Analysis for Petrobras Roncador Field Development

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractPetrobras as the operator of the Roncador field located offshore Brazil plans to develop part of this field utilizing a semi-submersible unit located in approximately 1800 meters of water depth. The paper presents key engineering challenges, solutions, and lessons learned from the design and analysis of a large number of steel catenary risers (SCRs) attached to this floating production unit (FPU).To demonstrate the robustness of the SCR design, sensitivity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The use of SCR in deepwater developments is becoming more popular with a number of SCR's already installed offshore Brazil and in the Gulf of Mexico, and West Africa [8][9][10][11][12][13] . Current development of SCR technology has focused on better understanding of the touch down region and its interaction with the seabed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of SCR in deepwater developments is becoming more popular with a number of SCR's already installed offshore Brazil and in the Gulf of Mexico, and West Africa [8][9][10][11][12][13] . Current development of SCR technology has focused on better understanding of the touch down region and its interaction with the seabed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a vast amount of research considering the effects of sea currents, waves, and the movement of the floating production unit on the dynamics of the risers (Gonzales, Mourelle et al, 2005;Pereira, Morooka et al, 2007); comparatively, very little is found in the literature regarding the impact of the internal flow (Patel & Seyed, 1989;Valdivia, Morooka et al, 2007). The present paper describes the introduction of the internal flow forces on the numerical simulation of the dynamics of risers.…”
Section: Introductionmentioning
confidence: 99%
“…Na região de topo, é possível utilizar uma junta flexível (flex joint) ou uma mísula para reduzir as tensões resultantes, conforme ilustra a Figura 3.3. Na TDZ, as soluções seriam de aumentar o ângulo de topo ou de variar a espessura do riser (Gonzalez et al, 2005).…”
Section: Risersunclassified